A comparative study of the arazyme-based fusion proteins with various ligands for more effective targeting cancer therapy: an in-silico analysis - Rezvan Mehrab; Hamid Sedighian; Fattah Sotoodehnejadnematalahi; Raheleh Halabian; Abbas Ali Imani Fooladi (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: Recently, the use of immunotoxins for targeted cancer therapy has been proposed, to find new anticancer drugs with high efficacy on tumor cells with minimal side effects on normal cells. we designed and compared several arazyme (AraA)-based fusion proteins with different ligands to choose the best-targeted therapy for interleukin 13 receptor alpha 2 (IL13Rα2)-overexpressed cancer cells. For this purpose, IL13Rα2 was selected as a receptor and IL13 and IL13.E13K were evaluated as native and mutant ligands, respectively. In addition, Pep-1 and A2b11 were chosen as the peptide ligands for targeted cancer therapy. Experimental approach: Several bioinformatics servers were used for designing constructs and optimization. The structures of the chimeric proteins were predicted and verified by I-TASSER, Q-Mean, ProSA, Ramachandran plot, and Verify3D program. Physicochemical properties, toxicity, and antigenicity were predicted by ProtParam, ToxinPred, and VaxiJen. HawkDock, LigPlot+, and GROMACS software were used for docking and molecular dynamics simulation of the ligand-receptor interaction. Findings/Results: The in silico results showed AraA-A2b11 has higher values of confidence score and Q-mean score was obtained for high-resolution crystal structures. All chimeric proteins were stable, non-toxic, and non-antigenic. AraA-(A(EAAAK)4ALEA(EAAAK)4A)2-IL13 retained its natural structure and based on ligand-receptor docking and molecular dynamic analysis, the binding ability of AraA-(A(EAAAK)4ALEA(EAAAK)4A)2-IL13 to IL13Rα2 was sufficiently strong. Conclusion and implications: Based on the bioinformatics result AraA-(A(EAAAK)4ALEA(EAAAK)4A)2-IL13 was a stable fusion protein with two separate domains and high affinity with the IL13Rα2 receptor. Therefore, AraA-(A(EAAAK)4ALEA(EAAAK)4A)2-IL13 fusion protein could be a new potent candidate for target cancer therapy.